EVALUATION OF VITAMIN-D LEVELS IN CHILDREN WITH TYPE-1 DIABETES MELLITUS - YADAVELLI, PRITHVI; VADE, VAMSHIDHAR REDDY; DEVINENI, SATYASRI (International Journal of Current Pharmaceutical Research, 2023)
Objective: Vitamin D supplementation during pregnancy and early childhood decreases the risk of autoimmune diabetes, and perhaps even after the onset of diabetes, it may improve glycemic control. Hence, the present study focuses on evaluating vitamin D levels in type-1 DM. Methods: It is a case-control study conducted on children aged from 6 y to 15 y who presented with type 1 DM and were admitted to the Department of Pediatrics, Dr. Patnam Mahender Reddy Institute of Medical Sciences, Chevella. Diabetic Mellitus was studied using a predesigned and pre-tested proforma. 100 children in the age group of 6-15 y were included, further divided into two groups. Children with Type 1 DM were enrolled as cases, while the normal children were enrolled as controls. Information was collected from the patient or attender or relative about the sociodemographic profile, dietary intake, and treatment history. A detailed clinical examination of the child was conducted with exact anthropometric measurements. Metabolic profile was done by investigating fasting blood sugar, postprandial blood sugar, and glycosylated hemoglobin. Blood samples were collected from all participants for measurement of hematological parameters. A Minividas analyzer estimated vitamin D, the Chemiluminescence method. Results: Most children with Type 1 DM were 10-14 y old, and the mean age of the cases was 11.36. This study's female-to-male ratio was 1.3:1 (29 and 21), respectively. In this study, we found that 38(76%) children were in the deficiency range, the majority in the age group of 10-14 y, while 7(14%) children were in the insufficiency range, only 5(10%) were in the sufficiency range. The significant finding in this study was the mean Vitamin D level for cases was 16.81, while in comparison, controls had a mean Vitamin D level of 25.74; it was significant. Conclusion: The present study revealed that the prevalence of vitamin D deficiency and insufficiency among T1 diabetes children was very high.